Kebiasaan Anak Binaan Dalam Clothing Cleanliness (Kebersihan Pakaian) Yang Berkaitan Dengan Kesehatan di Lembaga Pembinaan Khusus Kelas 1 Kutoarjo - Farhan Anwarrul Anam; Ali Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Cleanliness is a state of being free from dirt such as dust, rubbish and unpleasant odors. Bad habits in maintaining cleanliness will cause disease or infection caused by viruses and bacteria. Bad habits in keeping clothes clean can become a breeding ground for viruses and bacteria, especially dirty and damp clothes. Poor clothing hygiene can cause diseases such as fungal infections, itching or skin cancer. A Special Child Development Institution is a place where children who have been found guilty by the court are placed to receive guidance with the aim of making the child better and realizing their mistakes. A foster child is a child who is 14 (fourteen) years old, but not yet 18 (eighteen) years old and is currently undergoing the formation process at a Special Children's Institution. Writing this journal uses descriptive qualitative research methods from the results of observations and literature studies. Qualitative research is based on findings, behavior, interviews, and this research does not use statistical procedures or other quantitative methods. It is hoped that this qualitative research can explain the habitual patterns of assisted children in maintaining clean clothes which are related to the health of the assisted children.